Langmuir-wave Excitation in Solar Wind Magnetic Holes - Jingting Liu; Daniel Verscharen; Jesse Coburn; Georgios Nicolaou; Xiangyu Wu; Wence Jiang; Oreste Pezzi; Francesco Pucci; Matteo Zuin; Christopher J. Owen; Hamish Reid (The Astrophysical Journal Letters, 2025)
Magnetic holes (MHs) are structures commonly observed in various space plasma environments throughout the solar system, including the solar wind. These structures are characterized by a localized decrease in magnetic field strength, coincident with an increase in plasma density. Previous observational studies in the solar wind link the presence of Langmuir waves to MHs, suggesting a strong correlation between these phenomena. We develop a model based on magnetic-moment conservation and its violation to explain the excitation of Langmuir waves in MHs. Our model illustrates that MHs induce changes in the electron velocity distribution function that emit electrostatic Langmuir waves due to the bump-on-tail instability. Using data from the Solar Orbiter spacecraft, we provide a comprehensive analysis of this process and test our predictions with observations. The consistency between our model and observations indicates that the proposed process is a viable mechanism for producing Langmuir waves in MHs in the solar wind.